Pengabdian Desa Wisata Sigap dan Tanggap Bencana Melalui Aplikasi Early Warning Sistem dan Pemetaan Kebencanaan di Desa Baturiti Tabanan - I GD Yudha Partama; I Dewa Gede Agung Pandawana; Dewa Gede Agung Gana Kumara (Cv. Utility Project Solution, 2022)
Baturiti Village Government continues to develop tourism by forming the Baturiti Bersemi Tourism Awareness Group (Pokdarwis), which actively manages, develops, and promotes existing Tourism Destinations (DTW) to explore natural potentials as new DTWs. The development of DTW, of course, does not only focus on branding and promotion. It can also accommodate service aspects, especially guaranteeing a sense of security and comfort when visiting Baturiti Village in realizing disaster-safe tourism. The implementation of this community partnership program uses a Knowledge Transfer approach through counselling, mentoring and training, Technology Transfer (TT) through participatory mapping activities, and Diffusion of Science and Technology through the creation of an Early Warning System (EWS) and WebGIS based on digital applications that can assist partners in understanding disaster. With the use of technology. The evaluation was carried out by conducting a social impact questionnaire, significantly increasing the empowerment and knowledge of partners in knowing areas/locations as well as DTWs that have potential disaster hazards with the results of increasing knowledge about disaster-prone locations, safe zones, gathering points, and disaster routes by 80-90% as well as increasing participant skills in the use of EWS applications.